Pemberdayaan Masyarakat Dengan Pengabdian KKN Di Desa Libunio Kecamatan Soa Kabupaten Ngada - Gado, Alfridus; Aburman, Bernadinus; Tan, Valentinus (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
The implementation of the Flores University KKN in 2023 will be carried out collectively, namely on 01-31 August 2023 with the theme